Challenges and Futures of Long-Term Care Industry after COVID-19 Pandemic - Yu, Jia (Psychosocial, Educational, and Economic Impacts of COVID-19, 2022)
COVID-19 pandemic has affected people’s daily life dramatically since December 2019. More than 211 million cases and 4.42 million deaths have been reported and confirmed all over the world. Long-term care facilities are taking the biggest hit during this pandemic, even after the spread-out of the vaccines. Globally, residents in long-term care facilities have experienced disproportionately high morbidity and mortality from COVID-19. Elderlies residing in long-term care facilities have the greatest susceptibility to COVID-19 and the poorest outcomes from infections. This chapter overviewed the insight, impact, and challenges of COVID-19 on the residential care homes in UK, US, and Australia and provided possible implications for the long-term care market post-pandemic.
Keywords: dept.eco

'How could I choose my health insurance plan?' Determinants of employer-sponsored health insurance plan selection: application of machine learning technique - Zhang, Yi; Yu, Jia (International Journal of Economics and Business Research, 2022)
Selecting the appropriate, reasonable, and affordable health insurance plan becomes a very important question to solve for both employers and employees. Our research tries to locate the factors determining private sector health insurance plan enrolment decision, and also provides a guideline to both private companies and employees on health insurance plan selection strategies. By using Kaiser Family Foundation Annual Employer Health Benefits Survey (KFF EHBS) data, we apply random decision forest machine learning methodology to study the determinants of employees' health insurance selection, as well as to compare the prediction accuracy among different methodologies. The results indicate: 1) the employees at large firms and the firms with higher eligible rate would tend to choose PPO plan; 2) employees who need family coverage would have different choices comparing employees who seek for single coverage only; 3) employer's contribution and annual total contribution to the health insurance plan are the most important determinants on employees' insurance selection. The conclusion also can provide some suggestions to insurance companies on health insurance package design for different types of employers and employees.
Keywords: HDP; PPO; dept.eco; health insurance; high-deductible health plan; logit regression; machine learning; peer-reviewed; random decision forest